English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

x-3=x+2
3x=x+3
6+x=8-2x
7x=3-x+3x-2
x-3x+5=4+x


and the quadratics
x^2+x=4x^2+4
x+8x^2=81+x^2+3x


thanks!!!

2007-01-13 17:26:13 · 6 answers · asked by Anonymous in Science & Mathematics Mathematics

6 answers

1. x-3=x+2
<=> 0x - 3 = 2 <=> no x is the root of this equation
2. 3x=x+3
<=> 2x = 3 <=> x = 3/2
3. 6+x=8-2x
<=> 3x = 2 <=> x = 2/3
4. 7x=3-x+3x-2
<=> 5x = 1 <=> x = 1/5
5. x-3x+5=4+x
<=> 3x = 1 <=> x = 1/3


6. x^2+x=4x^2+4
<=> 3x^2 - x + 4 = 0
delta = 1 - 3*4*4 < 0
thus this equation has no real root
7. x+8x^2=81+x^2+3x
<=> 7x^2 - 2x - 81 = 0
delta = 4 + 4*7*81 = 2272
sqrt(delta) = 4*sqrt(142)
x = (1 + 2sqrt(142)) / 7
or x = (1 - 2sqrt(142)) / 7

2007-01-13 18:47:53 · answer #1 · answered by James Chan 4 · 0 0

x-3=x+2-- no answer - change it to x - x = 5, which is 0 = 5, and that's not a true statement
3x=x+3 -- make it 2x = 3, and then x = 3/2 or 1.5
6+x=8-2x -- make it 3x = 2, which makes it x = 2/3 or about 0.667
7x=3-x+3x-2 -- that's 7x = 1 + 2x, which is 5x = 1. so x = 1/5 or 0.2
x-3x+5=4+x-- that's -2x + 5 = 4 + x, which is 1 = 3x, so x = 1/3 or about 0.333

x^2+x=4x^2+4
make it all equal to zero: 0 = 3x^2 - x + 4
it looks unfactorable to me, so do the quadratic formula, and you get:
x = 0.16666666666666666 plus or minus 1.1426091000668406(i)

x+8x^2=81+x^2+3x
set to zero: 0 = 7x^2 - 2x - 81
also unfactorable
so quadratic equation again, and your two possible x values are:
x = 3.5475357965179954, and x = -3.26182151080371

2007-01-13 17:46:20 · answer #2 · answered by car of boat 4 · 1 0

x - 3 = x + 2 is not solvable

3x = x+3 => 2x = 3 => x = 3/2

6 + x = 8 - 2x => 3x = 2 => x = 2/3

7x = 3 -x + 3x - 2 => 5x = 1 => x=1/5

x - 3x + 5 = 4 + x => 3x = 1 => x=1/3

3x^2 - x - 4=0
x^2 - 1/3 x - 4/3 = 0
x^2 - 1/3x + (1/6)^2 - (1/6)^2 - 4/3 = 0
(x - 1/6)^2 - (1/36 + 4/3) = 0
(x- 1/6)^2 - (49/36) = 0
(x - 1/6 - 7/6)(x - 1/6 + 7/6) = 0
(x - 4/3)(x + 1) = 0
x=4/3
x= - 1

7x^2 - 2x -81 = 0
x^2 - 2/7x -81/7 = 0
x^2 - 2/7x + (1/7)^2 - (1/7)^2 - 81/7 = 0
(x - 1/7)^2 - (1/49 + 567/49) = 0
(x - 1/7 - sqrt(568)/7)(x - 1/7 + sqrt(568)/7) = 0
x = (1 + sqrt(568))/7
x = (1 - sqrt(568))/7

yw

2007-01-13 17:41:33 · answer #3 · answered by Anonymous · 0 1

x-3=x+2
Add 3 to both sides: x=x+5
Subtract x from both sides: 0=5

3x=x+3
Subtract x from both sides: 2x=3
Divide both sides by 2: x=3/2

6+x=8-2x
x=2-2x
3x=2
x=3/2

7x=3-x-3x-2
7x=1-4x
11x=1
x=1/11

x-3x+5=4+x
-2x+5=4+x
-2x=-1+x
-3x=-1
x=1/3

2007-01-13 17:42:18 · answer #4 · answered by Anonymous · 0 0

this would seem complicated, notwithstanding it truly is definitely extremely undemanding. i visit do quantity 2 for you because that is the hardest. 2(6x+3)=3(2x+12) a million. you want to distribute both and the three. this provides you: 12x+6=6x+36 2. Now you want to get "x" to one fringe of the equation and the each thing else to the different. Subtract 6x from each and each facet. You get: 6x+6=36 once it really is done, you want to subtract the "6" from each and each facet. 6x=36 3. Now you want to sparkling up for "x" by technique of dividing each and each facet by technique of 6. this provides you "x'' on one facet. 36 divided by technique of 6 = 6 the answer is x=6 question a million is x=-3 question 2 is x=6 question 3 is x=-3 desire that made experience !

2016-11-23 17:12:20 · answer #5 · answered by Anonymous · 0 0

C'mon!!!!! What grade are you in???

2007-01-14 03:30:32 · answer #6 · answered by Anonymous · 0 0

fedest.com, questions and answers